Expanding the Library of 2-Phenylbenzotellurazoles: Red-Shifting Effect of Ethoxy Functionalities on the UV/Vis Absorption Properties - Romito, Deborah; Amendolare, Leonardo; Kalathil, Krishnan K.; Bonifazi, Davide (Synthesis, 2022)
This work describes the high-yield synthesis of a novel series of benzotellurazoles bearing a phenyl ring in 2-position, which is differently functionalized with ethoxy chains. Changing the number and the position of these functional groups determines differences in the self-assembly in the solid state, as well as in the photophysical properties of the targeted molecules. As anticipated by theoretical calculations of the HOMO-LUMO gap of each molecule, the presence of ethoxy chains in o- and p-positions determines up to 20 nm red-shifts in the absorption peaks, when compared to unsubstituted benzotellurazole. Similarly, more significant changes are observed in the chemical shifts of 125Te NMR spectra for those derivatives bearing o- and p-ethoxy functionalization.
Keywords: benzo-1,3-tellurazoles; dehydrative cyclization; XRD analysis; UV/Vis investigation; 125Te NMR